Un viatge a l’infern: «Nit i boira» de Mercè Rodoreda - Campillo, Maria (Caplletra. Revista Internacional de Filologia, 2004)
The story «Nit i boira» by Mercè Rodoreda is one of the first literary texts written after the liberation of the German concentration camps. The author, who did not experience the camps first hand, is able to capture their essential characteristics using two “fundamental” paradigms: death and hell, as Paul Celan and Primo Levi did during the same era.